CONTEMPORARY APPROACHES IN ASSESSMENT OF STUDENTS IN HIGH EDUCATION IN CASE OF DIGITAL EDUCATION - Arslonbekova, Rano ("Science Shine" International scientific journal, 2024)
Abstract: This paper describes the assessment and its role in education. The authors draws attention to assessment of learning in this highly technological society which challenges both learners and students. Personal experiences of teachers in assessment of students for and after learning is explained. It elaborates on the use of learning management systems in the state university. There is reference to research studies on this topic and gives a thorough understanding of the concepts. The article concludes with recommendations and further actions for the readers to take to improve teaching and assessment of students.